2020
DOI: 10.1038/s41392-020-0144-8
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 is a direct target of cancer-FOXP3 in pancreatic ductal adenocarcinoma (PDAC), and combined immunotherapy with antibodies against PD-L1 and CCL5 is effective in the treatment of PDAC

Abstract: High expression of PD-L1 marks the poor prognosis of pancreatic ductal adenocarcinomas (PDAC). However, the regulatory mechanism of PD-L1 remains elusive. We recently reported that cancer Forkhead box protein 3 (Cancer-FOXP3 or C-FOXP3) promoted immune evasion of PDAC by recruiting Treg cells into PDAC via upregulation of CCL5. In this study, we confirmed that PD-L1 was overexpressed in PDAC samples from two independent cohorts of patients with radical resection. Moreover, C-FOXP3 was colocalized and correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 32 publications
3
63
0
Order By: Relevance
“…In many cancers, the interaction of costimulatory molecules on T lymphocytes with the tumor-associated membrane-bound protein PD-L1 can lead to apoptosis of activated T cells. Tumor-associated PD-L1 expression was reported to increase the apoptosis of activated T lymphocytes and assist cancer cells in escaping immune surveillance [30,46]. High expression of PD-L1 in pancreatic cancers is associated with a poor prognosis [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cancers, the interaction of costimulatory molecules on T lymphocytes with the tumor-associated membrane-bound protein PD-L1 can lead to apoptosis of activated T cells. Tumor-associated PD-L1 expression was reported to increase the apoptosis of activated T lymphocytes and assist cancer cells in escaping immune surveillance [30,46]. High expression of PD-L1 in pancreatic cancers is associated with a poor prognosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its chemotactic effect, S100A9 has been reported to be the endogenous ligand of Toll-like receptor 4 (TLR4) and to induce surface expression of PD-L1 in primary hematopoietic cells [28,29]. High expression of PD-L1 in PDAC was associated with poor prognosis [30]; however, the mechanism that regulates the expression of PD-L1 in PDAC is not clear. To verify the effect of S100A9 on the expression of PD-L1 on monocytes, we treated U937 cells with interferon gamma (IFN-γ)along with recombinant S100A9 and detected the surface expression of PD-L1 with flow cytometry.…”
Section: S100a9 Induces Surface Expression Of Pd-l1 In Monocytesmentioning
confidence: 99%
“…Elevated PD-L1/PD-1 levels were correlated with poor survival of cancer patients with NSCLC, 230 melanoma, 231 gastric cancer, 232 adrenocortical carcinoma, 233 breast cancer, 234 hepatic cancer, 235 and pancreatic cancer. 236,237 Specifically, PD-L1 expression in GBC (23%) was comparable to breast cancer (23%), urothelial cancer (20%), and pulmonary squamous cell carcinoma (27%). 238,239 Mody et al 240 found that 12% patients with tumor cell-expressing PD-L1 and 55% patients with tumor-infiltrating lymphocyte (TIL)-expressing PD-1 in a total of 203 GBC patients were associated with corresponding genetic aberrations and tumor mutational burden (TMB) status.…”
Section: Pd-1/pd-l1mentioning
confidence: 95%
“…In this context, measures that combine efforts to reduce inflammation and in parallel strengthen anti-tumor immune activities ( e.g. , immunotherapies) (as exemplified in ( 140 – 145 )), may have an even greater benefit in the clinic. This approach, that tilts the immune balance by down-regulating inflammation and increasing protective immunity, is practically feasible.…”
Section: Final Considerations and Perspectivesmentioning
confidence: 99%